ANALISIS KEPUASAN MASYARAKAT TERHADAP PELAYANAN PADA KP2TSP PROVINSI DIY - Suhada Suhada; Febriani Wahyusari Nurcahyanti (JURNAL ILMIAH EDUNOMIKA, 2023)
The One-Stop Integrated Licensing Service Office for the Special Region of Yogyakarta (KP2TSP DIY) is one of the agencies that continues to make improvements to improve the quality of service to the community. This study aims to see how far the services provided by the P2TSP office to the community. The results obtained will become the basis for improving the performance of the KP2TSP Service and will be used as material for reflection for future policy makers. The population in this study consisted of people who applied for permits and non-permits to the One-Stop Integrated Licensing Service Office for the Special Region of Yogyakarta (KP2TSP DIY) to obtain public services and a sample of 100 people was obtained. The questionnaire in this study aims to collect respondent data. Based on the results of the study, the Community Satisfaction Index (IKM) for the performance of KP2TSP DIY was in the Good category at 80.91. This result was enough to boost the achievement of KP2TSP because the IKM score rose 1.19 year-on-year. Keyword: Public Service, Elements of Service, Customer Satisfaction